Exclusive Breastfeeding Socialization: Social Impacts on the Core Family and Environmental Direction - Yogi Pasca Pratama; Bhimo Rizky Samudro; Ratna Dewi Kumalasari; Anang Pra Yogi (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2018)
The purpose of this activity is to improve information that is known by the community in relation to patterns, ways, mechanisms of Exclusive breastfeeding. Method of implementation in the form of counseling and socialization with material about Exclusive breastfeeding, the method is coupled with simulation activities and counseling process. Success in this activity is measured by the Focus Group Discussion process aimed at identifying obstacles to exclusive breastfeeding and how problem solving does not leave local wisdom. The results of the activities are the dissemination of information to health volunteers, which are expected to assist in disseminating information on the location of each residence and in the core family of the socialization participants. Keywords: Exclusive breastfeeding; Socialization; Health cadres.